Technology of formation of self-education competence in future teachers in modern conditions - Kyselova, Olesya (My University, 2023)
The article highlights the relevance of one of the urgent problems of modern pedagogical education. The formation of a new generation of teachers capable of lifelong self-education takes on special importance in modern conditions associated with the dynamic development of the information society, as well as in the situation of the spread of the coronavirus pandemic and the current state of war in Ukraine. The author defined the essence of the concept of «self-education of the future teacher», and identified the stages of self-education. The essence of self-education competence of the future teacher in the conditions of an open informational and educational environment and its structural components are presented: motivational-value, organizational, procedural-informational, and control-reflective. From the standpoint of the system approach, the properties of the competence of self-education are highlighted. The essence and didactic functions of the information-educational environment are revealed, and their influence on the self-education process of students is demonstrated. Attention is focused on its development as a key factor in the formation of the competence of self-education of the future teacher. Aspects of the transformation of the self-education activity of the future teacher in today's conditions are singled out. Internet services are presented to support each of its stages, as well as the advantages of existing educational platforms for the self-education of future teachers. The author justified the technology of formation of the specified competence in future teachers in modern conditions in the process of their professional training, characterized the approaches, directions, and guiding principles, the observance of which actualizes the achievement of a positive result of its implementation. The results of the experimental approbation of the developed technology in a higher educational institution are highlighted, which testify to its effectiveness and the feasibility of its introduction to the professional training of future teachers.
Kyselova O. Technology of formation of self-education competence in future teachers in modern conditions. / O. Kyselova // Modern pedagogical models of the formation and development of specifically scientific pedagogical phenomena : international collective monograph / edited by G. F. Ponomarova, A. A. Kharkivska, L. O. Petrychenko and other ; Municipal Establishment «Kharkiv Humanitarian Pedagogical Academy» of Kharkiv Regional Council. – Kharkiv-Praha : Publishing house OKTAN PRINT s.r.o., 2023. – P. 966–1005
Keywords: самоосвіта, компетентність самоосвіти, інформаційно-навчальне середовище, технологія, майбутній педагог; self-education, competence of self-education, information and educational environment, technology, future teacher